Method development and validation for the simultaneous determination of Ritonavir and Lopinavir by RP-HPLC and by UV- Spectrophotometry - B. Poornima; P. Jayachandra Reddy; D.S.S.N. Neelima (International Journal of Pharmacy and Analytical Research, 2022)
In the present work, RP-HPLC, UV spectroscopy method have been developed and validated for simultaneous determination of Ritonavir and Lopinavir in Tablet dosage form. The RP-HPLC method, C18 (250x4.6mm, i.d 5µm) as a stationary phase and mobile phase of methanol: water (85:15) at 1ml/min flow rate was used for the separation of both the compounds with a detection of 225nm. Linearity was obtai ned in the concentration range of 5-50µg/ml for Ritonavir and 20-200µg/ml for Lopinavir. The retention times of Ritonavir and Lopinavir was 4.8 and 5.9 min. In the second method i.e UV-Spectrophotometric simultaneous determination was done at 219nm and 245nm. Calibration graphs were established for 10-50µg/ml for Ritonavir and 20-200µg/ml for Lopinavir. These methods were economic and time saving. The newly developed methods were successfully utilized for the Quantitative estimation of Ritonavir and Lopinavir in pharmaceutical dosage forms, both the methods have been extensively validated as per ICH guidelines.